Influence of Antibiotic Administration on the Urinary Bladder Cancer Early Recurrence Rate. (8th November 2022) - Kowalski, Filip; Drewa, Tomasz; Adamowicz, Jan; Wilamowski, Jacek; Ostrowski, Adam; Ostrowska, Magdalena; Kamecki, Krzysztof; Miklas, Marcin; Szlaga, Michal; Mikolajczak, Witold; Pokrywczynska, Marta; Juszczak, Kajetan
Abstract : Bladder cancer tends to recur, making treatment one of the most expensive in oncology. The limited efficacy and high cost of adjuvant therapies in the treatment of bladder cancer prompt research on new drugs which could replace them. In vitro studies have established that antibiotics can have a cytostatic and cytotoxic effect on urinary bladder cancer cells. The objective of the study was to investigate the influence of antibiotics on the recurrence rate of bladder cancer. In a retrospective study, we analyzed a group of 199 patients with urinary bladder cancer from four urological centers. The study groups consisted of 40 patients who received ciprofloxacin and 83 patients who received beta-lactams as perioperative antimicrobial prophylaxis. The control group included 76 patients who did not get perioperative antimicrobial prophylaxis. The groups were analyzed for risk stratification, degree of malignancy, and size of the primary tumor. The average follow-up time was 24 months. The main focus of the study was to investigate the early recurrence rate of bladder cancer among studied groups, which could correlate with the effectiveness of currently used intravesical instillations. Additionally, cancer's early progression was examined. Regardless of the division used, the highest recurrence rate was found in the ciprofloxacin group. There were no statistical differences in the recurrence rate between patients who received beta-lactams and patients who did not receive any antibiotics. In addition, there were no differences due to the progression rate between the groups. Perioperative antibiotic administration does not influence the early recurrence rate in patients with nonmuscle invasive urothelial bladder cancer.